[OP.6C.05] NUTRITION AND INCIDENT HYPERTENSION IN A LARGE POPULATION OF FRENCH ADULTS: A PROSPECTIVE COHORT STUDY. (September 2017) - Lelong, H.; Kesse-guyot, E.; Galan, P.; Fezeu, L.; Hercberg, S.; Blacher, J.
Abstract : Objective: Hypertension is the most prevalent chronic disease worldwide. Dietary intake is pointed as one of the major determinants in his development. Data in the area are mostly obtained from cross-sectional studies. We aimed to investigate the association between 1) Nutritional factors, 2) Adherence to the Dietary Approach to Stop Hypertension (DASH) and the risk of incident hypertension in a large cohort study. Design and method: We prospectively examined the risk of hypertension among 80, 426 French adults participating in the NutriNet-Santé cohort study. Self-reported socio-demographic, lifestyle and health data were assessed at baseline and yearly, using a web-based questionnaire; three 24 h- records provided dietary data and validated score reflecting adherence to DASH were calculated. Associations between quartiles of nutrients, food groups, adherence to healthy diet and hypertension risk were assessed by multivariate (adjusted for age, sex, body mass index, family history of hypertension, sociodemographic and lifestyle factors) Cox proportional hazards models. Results: During a mean follow-up of 3.4 ± 2.1 years, 2, 413 incident cases of hypertension were documented. Among nutrients, those whose intakes were associated with hypertension risk were (Q4 vs. Q1) sodium: hazard ratio (HR) HR = 1.17 (95% CI, 1.02–1.35), potassium: HR = 0.82 (95% CI, 0.72–0.94), animal protein: HR = 1.26 (95% CI, 1.11–1.43), vegetable protein: HR = 0.85 (95% CI, 0.75–0.95), fiber: HR = 0.81 (95% CI), magnesium: HR = 0.77 (95% CI, 0.67–0.89). Among food groups, consumption of fruits and vegetables, whole grain, legumes and nuts were associated with lower risk of hypertension [HRs = 0.85 (95% CI, 0.74–0.97); 0.84 (95% CI, 0.76–0.93); 0.87 (95% CI, 0.76–1.00); 0.72 (95% CI, 0.63–0.83), respectively] and meat consumption with a greater risk (HR = 1.25 (95% CI, 1.11–0.42)). Adherence to the DASH was inversely associated with incident hypertension: HR = 0.66 (95% CI, 0.58–0.75). Conclusions: Our results confirmed the association of several nutrients and food groups intake and incident hypertension, and highlighted that adopting a global healthy diet could strongly contribute to the prevention of hypertension.